Treatment of Acute Myeloid Leukemia in the Era of Genomics—Achievements and Persisting Challenges - Green, Steven D.; Konig, Heiko (Frontiers in Genetics, 2020)
Acute Myeloid Leukemia (AML) represents a malignant disorder of the hematopoietic system that is mainly characterized by rapid proliferation, dysregulated apoptosis and impaired differentiation of leukemic blasts. For several decades, the diagnostic approach in AML was largely based on histologic characteristics with only little impact on the treatment-decision making process. This perspective has drastically changed within the past years due to the advent of novel molecular technologies, such as whole genome next-generation sequencing (NGS), and the resulting knowledge gain in AML biology and pathogenesis. After more than 4 decades of intensive chemotherapy as a “one-size fits all” concept, several targeted agents have recently been approved for the treatment of AML, either as single agents or as part of combined treatment regimens. Several other compounds, directed against regulators of apoptotic, epigenetic or micro-environmental pathways, as well as modulators of the immune system, are currently in development and being investigated in clinical trials. The constant progress in AML research has started to produce improved survival rates and fueled hopes that a once rapidly fatal disease can be transformed into a chronic condition. In this review, the authors provide a summary of recent advances in the development of targeted AML therapies and discuss persistent challenges.